2010
DOI: 10.1111/j.1365-2427.2009.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish spawning in a large temperate floodplain: the role of flooding and temperature

Abstract: 1. Floodplains are a key habitat for foraging, spawning and as a nursery for many riverine fish species. The lower Volga floodplains (Russian Federation) are still relatively undisturbed, while in Europe and North America, about 90% of floodplains have effectively been lost. 2. We examined relationships between the extent and timing of the spring flood, lateral spawning movements of fish species and timing and duration of spawning in the floodplain by sampling during spring 2006 and 2007. 3. Only the spawning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…Floodplains and lowlands inundated in spring provide relatively warmer water than in the river channel. Such areas are widely used by early foraging fry (Górski et al 2010). In the case of some freshwater fish species, a relationship was observed between the flood frequency and the efficiency of natural spawning (Petr 2005).…”
Section: Identification Of Ecosystem Servicesmentioning
confidence: 99%
“…Floodplains and lowlands inundated in spring provide relatively warmer water than in the river channel. Such areas are widely used by early foraging fry (Górski et al 2010). In the case of some freshwater fish species, a relationship was observed between the flood frequency and the efficiency of natural spawning (Petr 2005).…”
Section: Identification Of Ecosystem Servicesmentioning
confidence: 99%
“…The value of floods for fish spawning and growth has been discussed by many authors (Welcomme, 1979;Trifonova, 1983;Balcombe and Arthington, 2009;Górski et al, 2010) with their timing, duration, and extent suggested as the determining factors. Seasonal flooding may increase connectivity between floodplain water bodies and facilitate the exchange of nutrients, organisms and energy between aquatic and terrestrial compartments of river ecosystems (Thomaz et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Methods of habitat suitability modeling are experiencing increasing popularity in the evaluation of ecological flow (Aadland, 1993;Lamouroux and Capra, 2002;Lamouroux and Souchon, 2002;Lee et al, 2006Lee et al, , 2010Chaput-Bardy et al, 2009;Colvin et al, 2009;Barletta et al, 2010;Freitas et al, 2010;Gorski et al, 2010;Hermoso et al, 2010;Jimenez-Segura et al, 2010). The most classical of these is the instream flow incremental methodology (IFIM) developed by the U.S.…”
Section: Introductionmentioning
confidence: 98%